Comparison of Pharmacokinetics and Safety of Voriconazole Intravenous-to-Oral Switch in Immunocompromised Adolescents and Healthy Adults - Driscoll, Timothy A. (American Society for Microbiology, 2011)

(untitled)
The current voriconazole dosing recommendation in adolescents is based on limited efficacy and pharmacokinetic data. To confirm the appropriateness of dosing adolescents like adults, a pharmacokinetic study was conducted in 26 immunocompromised adolescents aged 12 to <17 years following intravenous (IV) voriconazole to oral switch regimens: 6 mg/kg IV every 12 h (q12h) on day 1 followed by 4 mg/kg IV q12h, then switched to 300 mg orally q12h. Area under the curve over a 12-hour dosing interval (AUC(0–12)) was calculated using a noncompartmental method and compared to the value for adults receiving the same dosing regimens. On average, the AUC(0–12) in adolescents after the first loading dose on day 1 and at steady state during IV treatment were 9.14 and 22.4 μg·h/ml, respectively (approximately 34% and 36% lower, respectively, than values for adults). At steady state during oral treatment, adolescents also had lower average exposure than adults (16.7 versus 34.0 μg·h/ml). Larger intersubject variability was observed in adolescents than in adults. There was a slight trend for some young adolescents with low body weight to have lower voriconazole exposure. It is likely that these young adolescents may metabolize voriconazole more similarly to children than to adults. Overall, with the same dosing regimens, voriconazole exposures in the majority of adolescents were comparable to those in adults. The young adolescents with low body weight during the transitioning period from childhood to adolescence (e.g., 12 to 14 years old) may need to receive higher doses to match the adult exposures. Safety of voriconazole in adolescents was consistent with the known safety profile of voriconazole.